1994
DOI: 10.3347/kjp.1994.32.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Nine cases of strongyloidiasis in Korea

Abstract: Nine cases of human infection with Strongyloides stercoralis are reported among patients admitted to the Seoul Paik and Sang-Kye Paik Hospitals, Inje University, from April 1990 to January 1992. The patients, 7 males and 2 females aged between 50 and 70, either had the history of long term use of steroids for management of arthritis, or were complicated with other chronic diseases such as hypertension, liver diseases, psychotic disorders, and gastrointestinal problems. All of the nine patients revealed rhabdit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…stercoralis is a common parasite of the intestinal tract, especially in tropical and subtropical areas (Genta, 1989;Siddiqui and Berk, 2001). In Korea, it has a low prevalence and several authors have occasionally reported it's presence on stool examination (Lee et al, 1994;Hong and Han, 1999). Excluding some papers published during the period of Josun Colonial Government, total 36 cases of human strongyloidiasis since 1945 have been recorded in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…stercoralis is a common parasite of the intestinal tract, especially in tropical and subtropical areas (Genta, 1989;Siddiqui and Berk, 2001). In Korea, it has a low prevalence and several authors have occasionally reported it's presence on stool examination (Lee et al, 1994;Hong and Han, 1999). Excluding some papers published during the period of Josun Colonial Government, total 36 cases of human strongyloidiasis since 1945 have been recorded in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In general, there is a low prevalence of Strongyloides infections in Korea as only few cases have been reported. Majority of reported cases belong to gastrointestinal strongyloidiasis 12 13 14 . A case of gastrointestinal hyperinfection with Strongyloides was confirmed by examination of gastric biopsy and gastroduodenal aspirate in an elderly lady receiving corticosteroid for arthritis 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Many individuals infected with SS are asymptomatic (Burke, 1978). Strongyloidiasis can occur in situations causing immunocompromisation, such as hematologic malignancies, usage of corticosteroids or other immunosuppressive therapies, HIV infection and malnutrition (Burke, 1978;Lee SK et al, 1994;Daubenton et al, 1998). If an immunocompromised individual is infected with SS, severe hyperinfection or disseminated disease with a high mortality rate could develop (Graeff-Teixeira et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Direct microscopic identification is difficult but rhabditiform larvae of SS may be differentiated from the others with characteristic features. The rhabditiform larvae measuring 300-350 µm, has short buccal cavity, hourglass-shaped esophagus and prominent genital primordium in the mid-section of the larvae (Lee SK et al, 1994;Graeff-Teixeira et al, 1997;Katz, 1999). Investigation of SS in duodenal fluid obtained by esophagogastroduodenoscopy, culture or mucosal biopsy is an option (Bannon et al, 1995).…”
Section: Discussionmentioning
confidence: 99%